GRHL3 Promotes Tumor Growth and Metastasis via the MEK Pathway in Colorectal Cancer. (30th November 2021) - Tan, Lin; Qu, Weiming; Wu, Dajun; Liu, Minji; Wang, Qian; Ai, Qiongjia; Hu, Hongsai; Chen, Min; Chen, Weishun; Zhou, Hongbing
Abstract : GRHL3 is a factor associated with a tumor, of which the molecular mechanism remains a further investigation. We explored the underlying mechanism of tumor-promoting effect of GRHL3 in colorectal cancer (CRC), which is involved in the MEK1/2 pathway. The expression of GRHL3 was measured in CRC and adjacent normal tissue using qPCR and immunohistochemical staining. Lentivirus-mediated knockdown expression of GRHL3 was performed in the CRC cell line HT29. Cell proliferation and metastasis were assayed in vitro, and tumorigenicity was investigated in vivo. We found higher GRHL3 expression in colorectal cancer, which was negatively correlated with patients' prognosis. Results from studies in vitro and in vivo indicated that downregulation of GRHL3 expression inhibited tumor growth and metastasis and inhibited the activation of the MEK1/2 pathway. The effect of GRHL3 downexpression was the same as that of MEK1/2 antagonists on suppression of tumor growth and metastasis. Our results suggested that GRHL3 may act as an oncogene to promote tumor growth and metastasis via the MEK pathway in colorectal cancer.